Metformin attenuates lung fibrosis development via NOX4 suppression. Issue 1 (December 2016) - Sato, Nahoko; Takasaka, Naoki; Yoshida, Masahiro; Tsubouchi, Kazuya; Minagawa, Shunsuke; Araya, Jun; Saito, Nayuta; Fujita, Yu; Kurita, Yusuke; Kobayashi, Kenji; Ito, Saburo; Hara, Hiromichi; et al.
Abstract Background Accumulation of profibrotic myofibroblasts in fibroblastic foci (FF) is a crucial process for development of fibrosis during idiopathic pulmonary fibrosis (IPF) pathogenesis, and transforming growth factor (TGF)-β plays a key regulatory role in myofibroblast differentiation. Reactive oxygen species (ROS) has been proposed to be involved in the mechanism for TGF-β-induced myofibroblast differentiation. Metformin is a biguanide antidiabetic medication and its pharmacological action is mediated through the activation of AMP-activated protein kinase (AMPK), which regulates not only energy homeostasis but also stress responses, including ROS. Therefore, we sought to investigate the inhibitory role of metformin in lung fibrosis development via modulating TGF-β signaling. Methods TGF-β-induced myofibroblast differentiation in lung fibroblasts (LF) was used for in vitro models. The anti-fibrotic role of metfromin was examined in a bleomycin (BLM)-induced lung fibrosis model. Results We found that TGF-β-induced myofibroblast differentiation was clearly inhibited by metformin treatment in LF. Metformin-mediated activation of AMPK was responsible for inhibiting TGF-β-induced NOX4 expression. NOX4 knockdown and N-acetylcysteine (NAC) treatment illustrated that NOX4-derived ROS generation was critical for TGF-β-induced SMAD phosphorylation and myofibroblast differentiation. BLM treatment induced development of lung fibrosis with concomitantly enhanced NOX4 expression and SMAD phosphorylation, which was efficiently inhibited by metformin. Increased NOX4 expression levels were also observed in FF of IPF lungs and LF isolated from IPF patients. Conclusions These findings suggest that metformin can be a promising anti-fibrotic modality of treatment for IPF affected by TGF-β.